Diverse Endogenous Antigens for Mouse Natural Killer T Cells: Self-Antigens That Are Not Glycosphingolipids - Pei, Bo (2010)
Natural killer T cells with an invariant antigen receptor (iNKT cells) represent a highly conserved and unique subset of T lymphocytes having properties of innate and adaptive immune cells. They have been reported to regulate a variety of immune responses, including the response to cancers and the development of autoimmunity. The development and activation of iNKT cells is dependent on self-antigens presented by the CD1d antigen-presenting molecule. It is widely believed that these self-antigens are glycosphingolipids (GSLs), molecules that contain ceramide as the lipid backbone. Here we used a variety of methods to show that mammalian antigens for mouse iNKT cells need not be GSLs, including the use of cell lines deficient in GSL biosynthesis and an inhibitor of GSL biosynthesis. Presentation of these antigens required the expression of CD1d molecules that could traffic to late endosomes, the site where self-antigen is acquired. Extracts of antigen-presenting cells (APCs) contain a self-antigen that could stimulate iNKT cells when added to plates coated with soluble, recombinant CD1d molecules. The antigen(s) in these extracts are resistant to sphingolipid-specific hydrolase digestion, consistent with the results using live APCs. Lyosphosphatidylcholine, a potential self-antigen that activated human iNKT cell lines, did not activate mouse iNKT cell hybridomas. Our data indicate that there may be more than one type of self-antigen for iNKT cells, that the self-antigens comparing mouse and human may not be conserved, and that the search to identify these molecules should not be confined to GSLs.